Staphylococcus epidermidis and biofilm‐associated neutrophils in chronic rhinosinusitis. A pilot study. Issue 6 (14th January 2016) - Marcinkiewicz, Janusz; Stręk, Paweł; Strus, Magdalena; Głowacki, Roman; Ciszek‐Lenda, Marta; Zagórska‐Świeży, Katarzyna; Gawda, Anna; Tomusiak, Anna
Summary: A key role of bacterial biofilm in the pathogenesis of chronic rhinosinusitis (CRS) with (CRSwNP) and without nasal polyps (CRSsNP) is commonly accepted. However, the impact of some bacterial species isolated from inflamed sinus mucosa on biofilm formation is unclear. In particular, the role of Staphylococcus epidermidis as aetiological agents of CRS is controversial. Moreover, the effect of biofilm formation on neutrophil infiltration and activity in CRSwNP calls for explanation. In this study, biofilms were found in three of 10 patients (mean age = 46 ± 14) with CRS undergoing endoscopic sinus surgery by means of scanning electron microscopy. Unexpectedly, S. epidermidis was the primary isolated bacteria and was also found to be present in all biofilm‐positive mucosa specimens, indicating its pivotal role in the pathogenesis of severe chronic infections associated with biofilm formation. We have also measured the activity of myeloperoxidase (MPO), the most abundant neutrophil enzyme, to demonstrate the presence of neutrophils in the samples tested. Our present results show that the level of MPO in CRS associated with biofilm is lower than that without biofilm. It may suggest either a low number of neutrophils or the presence of a type of neutrophils with compromised antimicrobial activity, described as biofilm‐associated neutrophils (BAN). Finally, we conclude that further studies with a large number of CRS cases should be performed to establish the association between S. epidermidis and other frequently isolated bacterial species from paranasal sinuses, with the severity of CRS, biofilm formation and the infiltration of BAN.